A Study of FAIES Method: Situational Approach Of Teaching Speaking Maritime English In Maritime Polytechnic Of North Sulawesi - Aliong Silalahi, Aliong (Politeknik Pelayaran Sulawesi Utara, 2021)
English communication skills in the areas of speaking, listening, reading and writing. However, in many students' minds communication means only interaction between the speaker and the listener. Teaching English at maritime universities and nautical colleges involves not only teaching the language and the sea-related terminology but also making the students aware of the cross-cultural issues and problems that they may encounter in their work on board ships. The best way of teaching is how the teacher, instructor and lecturer can choose and use the right teaching method. FAIES is one of an unique and wellknown method in teaching which can adapt with many situations in the classroom and makes the students feel easy to understand and study comfortably at the lesson especially in speaking English. According to Freud in Wollheim (1981), FAIES (First Aid in English System) is the teaching method to emphasize or stress on communication, which consist of directional approach, functional approach, situational approach and drilling technique. Maritime English is largely restricted to IMO Standard Marine Communication Phrases, which builds basic knowledge of English and has been drafted in a simplified version of maritime English. A multitude of new methodologies have explored and discussed in recent years in an attempt to approach the training and testing the proficiency of maritime English that meets the international standards laid out in STCW.